Correlation of brain imaging scale, comorbidities, and cognitive decline - Besin , Valentinus; Humardani, Farizky Martriano; Sadikin, Cindy (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Aging and increased life expectancy contribute to the rising prevalence of cognitive decline. Various diagnostic screening tools have been developed to assess cognitive function. While the impact of comorbidities on cognitive decline is well-established, further research is needed to understand their influence on diagnostic methods. This study explores the correlation between the MTA scale, Fazekas scale, and MoCA-INA, as well as the relationship between comorbidities and cognitive decline.Methods: This cross-sectional study used MRI scans to assess the Fazekas scale and MTA scale, while the MoCA-INA test was administered by a certified neurologist. Statistical analyses, including Spearman and ANOVA tests, were conducted to evaluate correlations between the MTA scale, Fazekas scale, and MoCA-INA scores. Chi-square and Pearson tests were applied to examine the relationship between comorbidities and cognitive decline.Results: The study sample included 18 males and 19 females. The MTA scale showed a significant negative correlation with cognitive decline (r = -0.513, p = 0.001). A combined analysis of MTA and Fazekas scale also yielded a significant negative correlation (r = -0.551, p = 0.002). Additionally, a significant correlation was found between stroke and small vessel disease with Fazekas scale (r = 0.342, p = 0.038).Conclusions: The MTA is a reliable scale for assessing cognitive decline. The combination of the Fazekas and MTA scale have a significant effect with cognitive decline. Stroke and small vessel disease influenced the Fazekas scale significantly. Further research is needed to explore the combined impact of brain imaging scales and comorbidities in dementia.